Enhanced biohydrogen generation through calcium peroxide engendered efficient ultrasonic disintegration of waste activated sludge in low temperature environment - Banu, J. Rajesh; Preethi; Gunasekaran, M.; Kumar, Vinod; Bhatia, Shashi Kant; Kumar, Gopalakrishnan (Elsevier, 2022)
Waste activated sludge is a renewable source for biohydrogen production, whereas the presence of complex biopolymers limits the hydrolysis step during this process, and thus pretreatment is required to disintegrate the sludge biomass. In this study, the feasibility of utilizing waste activated sludge to produce biohydrogen by improving the solubilization by means of thermo CaO2 engendered sonication disintegration (TCP-US) was studied. The optimized condition for extracellular polymeric substance (EPS) dissociation was obtained at the CaO2 dosage of 0.05 g/g SS at 70 °C. The maximum disintegration after EPS removal was achieved at the sonic specific energy input of 1612.8 kJ/kg TS with the maximum solubilization and SS reduction of 23.7% and 18.14%, respectively, which was higher than the US alone pretreatment. Thus, this solubilization yields higher biohydrogen production of 114.3 mLH2/gCOD in TCP-US sample.
Keywords: Solubilization; Dissociation; Disintegration; Biohydrogen; Hydrolysis; Extracellular polymeric substance